Smart Economy: The Analysis of Youngpreneurs Development towards the SMEs in East Java Province - satria, Dias; Wibowo, Joshi Maharani; Zahro, Fatimah (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractEast Java Province is one area in Indonesia with many potentials in the creative industry sector, especially SMEs. Unfortunately, SMEs growth in East Java Province is relatively slow because most of them still do not use technological tools. The reason is, SMEs is not attractive enough to the millennial generation and are still not digitized. This research was conducted to determine SMEs' potential digitalization to attract the millennial generation's interest in SMEs. The result showed three main obstacles to applying technology tools in the SMEs industry: marketing networking, branding and packaging, and product standardization. Apart from the obstacle, there are also three essential things to increase their interest in SMEs sectors, which are: SMEs community; local materials distribution; and optimization of the entrepreneurial mindset. A smart economy strategy can become a long-term economic investment to overcome every obstacle and stimulate the growth and Youngpreneur interest in the SMEs industry. Keywords:Millenial Generation, Smart Economy, SMEs